Effect of Oscimum basilicum on Formulation and Evaluation of Rapid Disintegrating Tablet of Lamotrigine - Akansha, Sharma (International Journal of Pharmaceutical & Biological Archive, 2012)
Effect of Oscimum basilicum on Formulation and Evaluation of Rapid Disintegrating Tablet of Lamotrigine